Magnetic raw data (SENSYS MXV3 system entire dataset) during campaign AFM-NIhK-2019-02, Ahlen-Falkenberger Moor (area 6), Germany - Moritz Mennenga; Anja Behrens (PANGAEA, 2024)
This is the measurement data from the geomagnetic prospection of the Ahlen-Falkenberger Moor (district of Cuxhaven, Lower Saxony, Germany) as part of the research project Preserved in the bog - relics of prehistoric settlement landscapes in the Elbe-Weser triangle funded by Niedersachsen Vorab. A total of about 800 ha were measured. The aim was to locate archaeological sites as well as landscape features. The measurements were carried out with a MXV3 system from Sensys with 6 FGM650/3 probes with a distance of 0.5m. Each probe consists of 2 sensors with 650mm basedistance and gives the gradient of the vertical component of the magnetic field (Z). The location was measured using a Stonex S10 GPS with Sapos HEPS correction data, resulting in a horizontal position accuracy of 0.01 – 0.02m and an elevation accuracy of 0.02 – 0.03m. The data were exported using DLMGPS (Sensys), whereby the coordinates of the individual probes are automatically determined from the central GPS position on the device. The data were exported without automatic track compensation. Due to the system, the position data is in UTM32/ETRS84 (EPSG 4647) and for conformity with PANGAEA also in WGS84 (EPSG 4326) (conversion is done with spTransform in R).
In: Mennenga, M; Behrens, A (2024): Magnetic raw data (SENSYS MXPDA and MXV3 system entire dataset), Ahlen-Falkenberger Moor, Germany - data series [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.963897